Physical activity in postmenopausal women - Szufnara-Wójcik, Gabriela; Boguszewski, Miłosz; Nizio, Norbert; Wyszyńska, Justyna; Drzał-Grabiec, Justyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Introduction. Menopause is the time when the female body goes through substantial endocrine changes resultant from the gradual phasing out of the reproductive activity of the ovaries. Consequently, post-menopausal women face some perimenopausal symptoms. These symptoms affect everyday physical and psychological functioning to various extent, and result in certain limitations. Aim. The aim of this paper was to study which limitations are most difficult for postmenopausal women, and how menopause symptoms affect women’s physical activity and satisfaction with life, as these are important components of quality of life. Materials and methods. The study involved 60 postmenopausal women. We used our own questionnaire. Results. We did not find the remaining relationships enumerated in research questions: the impact of menopausal syndromes on the frequency of physical activity, on its intensity, and on satisfaction with life, nor with the impact of subjective health on intensity of physical effort. Conclusions. We confirmed the relationship between intensity of physical effort and satisfaction with life and the relationship between subjective assessment of one’s health and the frequency of physical activity.
Keywords: menopause; postmenopause; physical activity